1 - CORSICA - Durand-Delga, Michel; Lahondère, Didier; Puccinelli, Alberto; Rossi, Philippe; Vellutini, Pierre (Ofioliti, 2007)
The Corsica Island is divided into two structural complexes which lie in contact with one another each others: the “Hercynian” (western) Corsica, the northern continuation of Sardinia, and the “Alpine” (eastern) Corsica, the southern continuation of the Ligurian Alps. The present position of the “Corsica-Sardinia microcontinent” is the consequence of its 30-40°C anticlockwise rotation with respect to stable Europe at the beginning of Miocene (cf. Argand, 1924, Fig. 22-27). At St. Florent, Aleria, Bonifacio and Ponte-Leccia, it is possible to observe some Mio-Pliocene relics sediments successive to this rotation.